Plant cell-like tip-growing polymer precipitate with structurally embedded multistimuli sensing ability - Park, Chan Jin; Ha, Jonghyun; Lee, Hae Ryung; Park, Keunhwan; Sun, Jeong Yun; Kim, Ho Young (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Soft systems that respond to external stimuli, such as heat, magnetic field, and light, find applications in a range of fields including soft robotics, energy harvesting, and biomedicine. However, most of the existing systems exhibit nondirectional, nastic movement as they can neither grow nor sense the direction of stimuli. In this regard, artificial systems are outperformed by organisms capable of directional growth in response to the sense of stimuli or tropic growth. Inspired by tropic growth schemes of plant cells and fungal hyphae, here we report an artificial multistimuli-responsive tropic tip-growing system based on nonsolvent-induced phase separation of polymer solution, where polymer precipitates as its solvent dissolves into surrounding nonsolvent. We provide a theoretical framework to predict the size and velocity of growing precipitates and demonstrate its capability of sensing the directions of gravity, mechanical contact, and light and adjusting its growing direction in response. Exploiting the embedded physical intelligence of sensing and responding to external stimuli, our soft material system achieves multiple tasks including printing 3D structures in a confined space, bypassing mechanical obstacles, and shielded transport of liquids within water.
Keywords: Gravitation; Plant Cells; Polymers; biomimetics; physical intelligence; polymer precipitation; tip growth